Meningkatkan Hasil Belajar IPA melalui Pembelajaran Kooperatif Tipe STAD pada Siswa Kelas V SDN 2 Panjang Utara Bandar Lampung - Jusnilawati, Jusnilawati (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study is to describe the STAD type cooperative learning method can improve science learning outcomes for fifth grade students of SD Negeri 2 Panjang Utara Bandar Lampung. The research method applied is Classroom Action Research which is carried out with reference to: planning, implementation, observation, and reflection for 3 cycles. The research subjects for the fifth grade students of SDN 2 Panjang Utara Bandar Lampung for the 2019/2020 academic year were 29 people. Based on the results of the study, it was found that the science learning of Grade V students of SDN 2 Panjang Utara Bandar Lampung for the academic year 2019/2020 through Cooperative Learning of the Stad type increased.